“La Iglesia es militante” Homenaje a la “Meditation sur l’Eglise” de Henri de Lubac, 60 años después de su publicación - Ledesma, Juan Pablo (Alpha Omega, 2014)
Summary: The Church is “militant”. This statement of Henri de Lubac, one of the greatest theologians of the twentieth century, is clearly developed in his “Meditation on the Church” (introduction). In this study I want to enter more deeply into this insight of the famous Jesuit theologian, showing how the Church is militant in her origin and in her history (1). She is militant in her purpose (2) and finally, She is militant in her consummation (3). Some images of the Church, taken from the patristic tradition, corroborate this intuition (conclusion).Sommario: La Chiesa è “militante”. Quest’affermazione di Henri de Lubac, uno dei più grandi teologi del ventesimo secolo, è chiaramente sviluppata nella sua “Meditazione sulla Chiesa” (introduzione). In questo studio voglio approfondire in questa intuizione del famoso teologo gesuita, mostrando come la Chiesa sia militante nella sua origine e nella sua storia (1), militante nel suo compito (2) e finalmente, militante nella sua consumazione (3). Alcuneimmagini della chiesa, prese dalla tradizione patristica, corroborano questa intuizione (conclusione).Key words: Church, militant Church, Kingdom of God, Kingdom of Christ, Henri de Lubac, Fathers of the Church, Gaudium et Spes, Benedict XVI, Pope Francis.Parole chiave: Chiesa, chiesa militante, Regno di Dio, Regno di Cristo, Henri de Lubac, Padri della Chiesa, Gaudium et Spes, Benedetto XVI, Papa Francesco.